2018
DOI: 10.1186/s12955-018-0943-6
|View full text |Cite
|
Sign up to set email alerts
|

Effect of psychosocial interventions on the quality of life of patients with colorectal cancer: a systematic review and meta-analysis

Abstract: BackgroundWe conducted a systematic review and meta-analysis of randomized controlled trials examining the effect of psychosocial interventions on the quality of life of patients with colorectal cancer.MethodsWe searched the main health-related databases for relevant papers. Then, we examined the titles and abstracts of the retrieved papers, applying exclusion criteria to filter out irrelevant papers; a more in-depth filtering process was then conducted by reading the full texts. Eight studies remained at the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0
3

Year Published

2019
2019
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 50 publications
3
20
0
3
Order By: Relevance
“…Beneficial effects on quality of life with psychosocial interventions (mainly face-to-face approaches) [ 112 ] have been described [ 113 ]. Also, interventions focused on enriching communication with CRC patients have also been carried out.…”
Section: Multidisciplinary Team and Comprehensive Interventions In Colorectal Cancer Patientsmentioning
confidence: 99%
“…Beneficial effects on quality of life with psychosocial interventions (mainly face-to-face approaches) [ 112 ] have been described [ 113 ]. Also, interventions focused on enriching communication with CRC patients have also been carried out.…”
Section: Multidisciplinary Team and Comprehensive Interventions In Colorectal Cancer Patientsmentioning
confidence: 99%
“…It has been found that psychosocial interventions can improve the quality of life of patients with CRC. Before using them, it is important to assess the physical functioning or severity of the symptoms (Son et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…These changes experienced by older individuals limit the ADL and negatively affect their quality of life. 6,7 In the 1970s, Nancy Roper, Winifred W. Logan and Alison J. Tierney developed a Nursing Model, based on ADL, that provides a systematic presentation of ADL and a rational method of approaching human beings with all dimensions to identify the importance of ADL. ADL presents individuals' activities that they carry out to maintain daily life.…”
Section: Barthel Index Of Adlmentioning
confidence: 99%